2013
DOI: 10.1002/hep.26540
|View full text |Cite
|
Sign up to set email alerts
|

Identification of driver genes in hepatocellular carcinoma by exome sequencing

Abstract: Genetic alterations in specific driver genes lead to disruption of cellular pathways and are critical events in the instigation and progression of hepatocellular carcinoma. As a prerequisite for individualized cancer treatment, we sought to characterize the landscape of recurrent somatic mutations in hepatocellular carcinoma. We performed whole exome sequencing on 87 hepatocellular carcinomas and matched normal adjacent tissues to anaverage coverage of 59x. The overall mutation rate was roughly 2 mutations per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
229
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(246 citation statements)
references
References 36 publications
14
229
2
1
Order By: Relevance
“…21 However, an extremely low frequency of mutation of this gene has been reported in human HCC. 5,6 In agreement with these findings, no mutations of Kras could be observed in 30 preneoplastic nodules. Kras mutations were found only in 1/14 eHCCs and 1/27 aHCCs.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…21 However, an extremely low frequency of mutation of this gene has been reported in human HCC. 5,6 In agreement with these findings, no mutations of Kras could be observed in 30 preneoplastic nodules. Kras mutations were found only in 1/14 eHCCs and 1/27 aHCCs.…”
Section: Resultssupporting
confidence: 76%
“…Dysregulation of the Wnt/b-catenin pathway and occurrence of activating mutations in CTNNB1 are among the most frequent alterations in human HCC (15%-33%). 5,6,9 However, whether CTNNB1 mutations occur at early stages of the carcinogenic process is unclear. Therefore, we investigated Ctnnb1 mutations in the same samples (38 preneoplastic lesions, 14 eHCCs, and 27 aHCCs) analyzed for Nrf2/ Keap1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous targeted sequencing efforts have come to markedly different mutation rates for KRAS in patients from different Asian and European countries, which may be associated with the aetiologies specific to patients from different locations. In sharp contrast, KRAS was not identified as significantly mutated gene in any HCC cancer genome sequencing projects [12][13][14][15][16][17][18] , underscoring the uniqueness between these two types of PLCs. Among 17 KRAS mutations discovered in our study, all mutations occur exclusively at codon 12, causing G-4D (seven), G-4V (six), G-4A (two) and G-4C (two) changes in the protein (Supplementary Data 3).…”
Section: Mutationmentioning
confidence: 95%
“…Therefore, other genes in Table 2 could be potential driver genes as well. Among these genes, two genes TP53 and ARID1A are also frequently mutated in HCC patients [12][13][14][15]17,18 , suggesting that these two types of PLCs may have both unique and shared molecular mechanisms in tumorigenesis. TP53 is mutated in 39 (38.2%) of this cohort of ICC patients, a frequency within the range of frequencies reported in some previous studies targeting TP53 in ICCs, but is substantially higher than many frequencies reported previously.…”
Section: Mutationmentioning
confidence: 99%
See 1 more Smart Citation